Demographic Inference of Divergence and Gene Exchange Between Castanopsis fabri and Castanopsis lamontii - Sun, Ye; Wen, Xiangying (Frontiers in Plant Science, 2020)
The cytoplasmic genome of one species may be replaced by that of another species without leaving any trace of past hybridization in its nuclear genome, which can thus confuse the inference of genealogical relationship and evolutionary history of many congeneric species. In this study, we used sequence variations of chloroplast DNA and restriction site-associated DNA to investigate gene exchange between Castanopsis fabri and Castanopsis lamontii, and to infer the divergence history of the two species by comparing different divergence models based on the joint allele frequency spectrum. We evaluated climatic niche similarity of the two species using climatic variables across their entire distribution range in subtropical China. Clear genetic differentiation was revealed between C. fabri and C. lamontii, and gene exchange between the two species was discovered as a consequence of secondary contact. The gene exchange rates were variable across the genome. Gene exchange could allow C. fabri to widen its habitat through pollen swamping and broaden its climatic niche, and the chloroplast genome of C. lamontii is captured by C. fabri during this process. These results further our understanding of the timing and contribution of gene exchange to species divergence in forests.